An advanced near real dynamic in vitro human stomach system to study gastric digestion and emptying of beef stew and cooked rice. Issue 5 (9th May 2019) - Wang, Jingjing; Wu, Peng; Liu, Minghui; Liao, Zhenkai; Wang, Yong; Dong, Zhizhong; Chen, Xiao Dong
Abstract : A near real dynamic in vitro human stomach (new DIVHS) system has recently been advanced in this study, based on the previous rope-driven in vitro human stomach model (RD-IV-HSM). Abstract : A near real dynamic in vitro human stomach (new DIVHS) system has recently been advanced in this study, based on the previous rope-driven in vitro human stomach model (RD-IV-HSM). The new DIVHS mainly consists of a J-shaped silicone human stomach model fabricated using 3D-printing technology which has a similar stomach morphology, dimension and wrinkled inner structure to those present in vivo, and an electromechanical instrument composed of a series of motors, rollers and eccentric wheels to produce peristaltic contractions. The simulated stomach system was able to generate consistent gastric emptying ratios of both the solid and liquid fractions in beef stew mixed with orange juice with that reported in vivo ( p > 0.05). By fitting the gastric retention data with a modified power-exponential model, the solid fractions showed an average emptying half-time ( t 1/2 ) of 74.1 min and a lag phase ( t lag ) of 36.3 min in the new DIVHS, similar to that obtained in vivo where the average values of t 1/2 and t lag were 75.8 min and 40.2 min, respectively. The performance of the new DIVHS was further validated by showing good qualitative matches of the gastric pH, particle size distribution and emptying profiles of cooked rice with the literature in vivo data. These results indicate that it is a reasonable approach to perform in vitro gastric digestion experiments using the new DIVHS, which is practically meaningful.